PENGARUH RISIKO KREDIT TERHADAP PROFITABILITAS PADA BANK KONVENSIONAL DI INDONESIA (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2019-2021) (JAPB, 2022)
This study aims to determine the effect of Credit Risk as measured by Non-Performing Loan Gross (NPL Gross) and Non-Performing Loan Net (NPL Net) on Profitability Levels as measured by Return on Assets (ROA), Return On Equity (ROE) and Net Profit Margin (NPM) at conventional banks listed on the Indonesia Stock Exchange for the 2019-2021 period. The method used in this study is a descriptive method with a quantitative approach which is carried out using external secondary data as research material. This research was conducted on banks listed on the Indonesia Stock Exchange by taking annual financial statements for 2019-2021. The data source of this research is secondary data in the form of banking financial statements. The sample used in this study was 16 banks listed on the IDX within three years from 2019-2021. The data analysis technique used in this study is the GeSCA (Generalized Structured Component Analysis) method. Based on the study results, it can be concluded that there is an influence of Credit Risk on Profitability in Banks listed on the Indonesia Stock Exchange. The magnitude of the influence of credit risk (X) on the profitability (Y) of banks listed on the Indonesia Stock Exchange can be seen from AFIT = 0.545, meaning that the AFIT value contributes 54.5% and other factors outside of the study influence the remaining 45.5%. Keywords: Bank, Credit Risk, Profitability, GesCA